Child protection systems international trends and orientations - Gilbert, Neil, 1940-; Parton, Nigel; Skivenes, Marit (New York ; Oxford : Oxford University Press, 2011)
This vital book is a comparative study of the social policies and professional practices that frame societal responses to the problems of child maltreatment in ten countries.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Child welfare; Child abuse